Formation of competence in the field of life safety of students based on the activity approach - E. R. Abdulina (Вестник Северо-Кавказского федерального университета, 2022)
Some approaches to the formation of competence in the field of life safety among students of higher educational institutions are considered. The elements of the activity approach used to form students competence in the study of individual sections of the course «Life Safety» are given. It is shown that the activity approach, including the participation of students in the Olympiad movement, contributes to the active formation of universal and professional competencies. The features and objectives of the Olympiad on life safety (II round of the All-Russian Student Olympiad on Life Safety) at the regional level are presented. Examples of tasks of various forms are given. Some features of the Olympiad in remote form are analyzed.